2009
DOI: 10.1007/s12206-009-0905-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a rectangular profile annular fin based on fixed fin height

Abstract: The optimum performance and fin length of a rectangular profile annular fin are presented using a variations separation method. For fixed fin height, the optimum fin length and efficiency are arbitrarily defined as those for which the heat loss is in the range between 90% and 99% of the maximum heat loss. The maximum heat loss, the maximum effectiveness, the minimum fin resistance, the optimum fin length and the optimum efficiency are presented as a function of the inside fluid convection characteristic number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Finally, a comparison was made between the optimum dimensions of the uniform fins and the dimensions of fins with minimal weight. Kang [6] method to determine the fin length of a rectangular profile fully wet annular fin to yield the optimum performance. In that study, the author concluded that, when considering the thermal conductivity to be constant, the optimum length and effectiveness are independent of the properties of the material used, whereas the optimum base thickness and the volume of the fin are inversely proportional to the thermal conductivity of the fin material.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a comparison was made between the optimum dimensions of the uniform fins and the dimensions of fins with minimal weight. Kang [6] method to determine the fin length of a rectangular profile fully wet annular fin to yield the optimum performance. In that study, the author concluded that, when considering the thermal conductivity to be constant, the optimum length and effectiveness are independent of the properties of the material used, whereas the optimum base thickness and the volume of the fin are inversely proportional to the thermal conductivity of the fin material.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous linear fin shape design problems were investigated to optimize the annular fin profiles with constant thermal properties. For example, a variation separation method was used by Kang [14] in determining the fin length of a fully wet annular rectangular fin to achieve optimal fin efficiency. They have concluded that when assuming constant thermal conductivity, the optimum length and effectiveness of fins are independent of the fin material, however, the optimum base thickness and the volume of the fin are inversely proportional to the fin conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…He found that the optimum heat loss, fin effectiveness, and the fin length increased linearly as the inside radius of the fin (tube radius) increased. In a contemporaneous paper, Kang [30] optimized the annular fin design based on a fixed fin height (the difference between the outer and inner radii of the fin ). An important conclusion emerging from this work was that the optimum fin length decreases as the fin base thickness increases.…”
Section: Introductionmentioning
confidence: 99%